2015
DOI: 10.3945/an.115.008268
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Neurocognitive Basis of Food Reward and the Control of Intake

Abstract: With the rising prevalence of obesity, hedonic eating has become an important theme in obesity research. Hedonic eating is thought to be that driven by the reward of food consumption and not metabolic need, and this has focused attention on the brain reward system and how its dysregulation may cause overeating and obesity. Here, we begin by examining the brain reward system and the evidence for its dysregulation in human obesity. We then consider the issue of how individuals are able to control their hedonic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 183 publications
(192 reference statements)
2
77
0
6
Order By: Relevance
“…In agreement with our hypothesis, the present investigation evidenced associations of DA gene methylation patterns with BMI, AO, and carbohydrate intake, which might serve as epigenetic biomarkers of feeding behavior attitudes, excessive adiposity, and fat deposition. These results are consistent with the fact that disruptions in dopaminergic synapse may lead to overconsumption by altering the rewarding effects elicited by palatable foods (Ziauddeen et al., 2015). In this sense, it has been reported that high‐carbohydrate diets can trigger addictive‐like neurochemical and behavioral responses in vulnerable individuals, contributing to weight gain (Lennerz & Lennerz, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our hypothesis, the present investigation evidenced associations of DA gene methylation patterns with BMI, AO, and carbohydrate intake, which might serve as epigenetic biomarkers of feeding behavior attitudes, excessive adiposity, and fat deposition. These results are consistent with the fact that disruptions in dopaminergic synapse may lead to overconsumption by altering the rewarding effects elicited by palatable foods (Ziauddeen et al., 2015). In this sense, it has been reported that high‐carbohydrate diets can trigger addictive‐like neurochemical and behavioral responses in vulnerable individuals, contributing to weight gain (Lennerz & Lennerz, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Besides homeostatic processes concerning energy and nutrient metabolic control, eating behavior is also regulated by hedonic (nonhomeostatic) mechanisms (Hernández Ruiz de Eguilaz et al., 2018), which are thought to be driven by the rewarding properties of foods and specific nutritional and behavioral afferent signals (Ziauddeen, Alonso‐Alonso, Hill, Kelley, & Khan, 2015). In this context, it has been reported that similar to alcohol and other drugs of abuse, highly palatable foods (rich in sugars and fat) can trigger neuroadaptive responses in brain reward circuitries (Alonso‐Alonso et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To protect children and those vulnerable to obesity, clinicians and others working with young people should make consistent, comprehensive concerted efforts to discourage hedonic eating [43], especially given that eating can become an addiction under certain circumstances, as with other behaviors [44]. Some consideration that the brain is either impaired to start off with, or undergoes structural changes must be considered in light of the finding that despite it becoming increasingly known that added sugars can have detrimental effects on health, people persist in consuming them in excess [45].…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, obesity is not caused by a single behavior, for example, overeating (Elman et al, 2006;Stice et al, 2011b;Ziauddeen et al, 2015), but falls into different behavioral categories. One example comes from binge-eating disorder with and without obesity.…”
Section: Obesity-related Changes In Striatal Reward Processingmentioning
confidence: 99%